2007
DOI: 10.1063/1.2785942
|View full text |Cite
|
Sign up to set email alerts
|

Formation of self-organized platinum nanoparticles and their microphotoluminescence enhancement in the visible light region

Abstract: Formation of Pt nanoparticles or nanoisland films as a function of annealing temperature, initial thickness, underlying substrates, and annealing process is investigated. Using microphotoluminescence ͑PL͒ measurement, we find great enhancement of self-emission in visible spectrum from Pt nanoparticles. The integral intensity of the micro-PL of the 49.38 nm Pt nanoparticles is 38 times of that of the Pt thin film. In addition, the peak wavelength varies from 554 to 615 nm as the surface morphology of Pt changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…3 . Due to the difference of the thermal expansion coefficient between the substrates and Pt films, when the initial thickness of Pt films is in the scale of nanometers, the compressive stress induced by annealing and the Ostwald ripening mechanism would cause the Pt films to form isolated particles [ 18 ]. With increasing the Pt mass-thickness from 2 to 8 nm, the particle size increases from 20 to 200 nm, while the inter-particle distance of the Pt NPs increases from 20 to 150 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 . Due to the difference of the thermal expansion coefficient between the substrates and Pt films, when the initial thickness of Pt films is in the scale of nanometers, the compressive stress induced by annealing and the Ostwald ripening mechanism would cause the Pt films to form isolated particles [ 18 ]. With increasing the Pt mass-thickness from 2 to 8 nm, the particle size increases from 20 to 200 nm, while the inter-particle distance of the Pt NPs increases from 20 to 150 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It is also found that the particle shape changes from sphericity to ellipse when the Pt mass-thickness increases from 2 to 6 nm, and they form a semi-continuous percolation film when the mass-thickness exceeds 8 nm. Obviously, the size, distance and shape of Pt NPs can be easily controlled by varying the initial mass-thicknesses of the Pt films, which will be in favor for tuning the characteristics of Pt LSP [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nano-island films of Pt nanoparticles have also shown micro-photoluminescence emission in the visible light region. 26 Platinum nanoparticles embedded in a silica matrix have been previously synthesized. [27][28][29] We recently studied the PL emission characteristics of Pt-ncs embedded in SiO 2 and observed quenching of emission for nanoparticles larger than 2 nm in diameter, as plasmonic properties started to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Indium atoms easily gather into clusters. Secondly, InN preferentially nucleated on In-rich regions according to the gassolid (G-S) mode [14][15][16][17], then the neighboring InN islands coalescence according to the Volmer-Weber (V-W) mode [18,19]. Finally, the InN nanocolumns grew up on the isolated InN islands according to the Stranski-Krastanow (S-K) mode.…”
Section: Resultsmentioning
confidence: 99%